Effect of partial replacement of dietary fish meal with soybean meal on some hematological and serum biochemical parameters of juvenile Beluga, Huso huso - Hosseini, S.A.; Khajepour, F. (2013)
This study was conducted to investigate the effects of partial replacement of dietary fish meal with soybean meal (SBM) on some blood and serum parameters of Beluga (Huso huso) juveniles. Three isonitrogenic and isoenergetic diets, as SBM1 (Soybean meal protein (SBP):Fishmeal Protein (FP) = 1:3), SBM2 (SBP:FP = 2:3) and SBM3 (SBP:FP = 1:1) were fed to triplicate groups of fish. After 8 weeks feeding on the experimental diets, blood parameters were measured. The results revealed that of partial replacement of dietary fish meal with soybean meal had no effect on, leukocyte (WBC) levels, red blood cell counts (RBC), mean corpuscular volume (MCV), mean cellular hemoglobin (MCH) or mean cell hemoglobin concentration (MCHC) (P>0.05). However, hemoglobin (Hb) concentration and hematocrit (Hct) values were significantly decreased by increasing dietary soybean meal (P<0.05). Serum glucose had significantly affected by increasing soybean meal. While total protein, phosphorus or calcium remained unaffected between groups. These results indicated that partial replacement of dietary fish meal with soybean meal could affect on some haematological and biochemical parameters in beluga which should be studied in future.